Improvement of Open Source Software Usability: An Empirical Evaluation from Developers' Perspective. (27th July 2010) - Raza, Arif; Capretz, Luiz F.; Ahmed, Faheem
Abstract : User satisfaction has always been important for software success whether it is Open Source Software (OSS) or closed proprietary software. Even though we do not presume that OSS always has poor usability, as there are examples of good usable open source software, it would still be agreed that OSS usability has room for further improvement. This paper presents an empirical investigation to study the impact of some key factors on OSS usability from developers' points of view. This is one of the series of four studies that we are conducting regarding improvement of OSS usability from OSS developers, users, contributors, and industry perspectives. The research model of this empirical investigation studies and establishes the relationship between the key usability factors from developers' perspective and OSS usability. A data set of 106 OSS developers from 18 open source projects of varied size has been used to study the research model. The results of this study provide empirical evidence that the studied key factors play a significant role in improving OSS usability.